Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika Materi Perkalian Bersusun Kelas IV SD Negeri 1 Anjongan - Andre, Andre (Jurnal Multidisiplin Indonesia, 2024)
His research is a descriptive qualitative research using a checklist sheet instrument. Researchers in this study collected data with documentation. The main data source used in this study was class IV students, totaliting 30 students and the answers of class IV students for the 2023/2024 academic year. The results showed that there were 4 types of errors made by students including conceptual errors, operational errors, principle errors and careless errors. Based on the analysis conducted by the researcher, as many as 26 out of 30 students or 62% of students made conceptual errors, as many as 27 of 30 students or 67,3 % made operational errors, as many as 19 of 30 students or 28% made principle and as many as 6 out of 30 students or 4,6% made careless mistakes in solving math problem on multiplication material. The types of errors made by students were error in understanding the multiplication cocept, multiplication procedure errors and error in using arithmetic operations.